2015
DOI: 10.1002/14651858.cd004848.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Common antiepileptic drugs in pregnancy in women with epilepsy

Abstract: The editorial group responsible for this previously published document have withdrawn it from publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
7
0
5
Order By: Relevance
“…Bununla birlikte, epilepsi hastası olan gebelerin yaklaşık yarısının bu dönemde nöbet geçirmedikleri görülebilmektedir. [10,11] Melikova ve ark.nın [12] [13][14][15][16] Folik asit fetusun santral sinir sisteminin gelişiminde gereklidir, özellikle hızlı hücre bölünmesi gebeliğin ilk trimesterinde önemlidir. Folik asit eksikliği olan gebelerin bebeklerinde, düşük doğum ağırlığı, prematür doğum, nöral tüp defekti gibi sorunların görülme sıklığı artmaktadır.…”
Section: Discussionunclassified
“…Bununla birlikte, epilepsi hastası olan gebelerin yaklaşık yarısının bu dönemde nöbet geçirmedikleri görülebilmektedir. [10,11] Melikova ve ark.nın [12] [13][14][15][16] Folik asit fetusun santral sinir sisteminin gelişiminde gereklidir, özellikle hızlı hücre bölünmesi gebeliğin ilk trimesterinde önemlidir. Folik asit eksikliği olan gebelerin bebeklerinde, düşük doğum ağırlığı, prematür doğum, nöral tüp defekti gibi sorunların görülme sıklığı artmaktadır.…”
Section: Discussionunclassified
“…6 A Cochrane review of 22 observational prospective cohort studies and six register studies confirmed the observation of poorer neurodevelopmental outcomes of pregnancies exposed to valproate. 7 The effect is dose related and exacerbated by polytherapy. In 2015, the European Registry of Antiepileptic Drugs and Pregnancy (EURAP) study group (an International registry of antiepileptic drugs and pregnancy) published on 1,224 pregnancies where valproate was taken alone and a further 364 where it was taken alongside another epilepsy drug.…”
Section: The Evidencementioning
confidence: 99%
“…Bu bulgular literatür ile uyumlu olup, konvülsif nöbetlerin teratojenik etkisinin daha fazla olduğunu düşündürmektedir. [10][11][12][13] Daha önceki çalışmalarda, epilepsi tanılı kadın-ların üçte birinde, gebelik sırasında nöbet sıklığında artma olduğu rapor edilmiştir.…”
Section: Nöbet Tipiunclassified